First-aid handbook for teachers 2.0 (2nd part) - Medina Domínguez, Javier; Robles Carrascosa, Ana (Avances en Supervisión Educativa, 2010)
It is a permanent challenge for teachers to perform well in a technological society. Above their personal specialization on a subject, there is a new stage with endless possibilities only limited by the creativity of the teacher and the response of a class of students. In the former chapter we analysed the didactic possibilities of blogs, forums and chat lines and we also offered some strategies for the teaching work with pictures and videos. On this occasion, we will turn our attention to recognize and assess the didactic exploitation of the tool to elaborate conceptual outlines and interactive wall-charts.